The air matters – sleeve air cavity as a marker guiding image-guided helical tomotherapy to target cervical cancer - Jan, Ya-Ting; Chang, Chih-Long; Tai, Hung-Chi; Huang, Yu-Chuen; Liao, Chia-Ling; Chen, Yu-Jen (Journal of Contemporary Brachytherapy, 2016)
Purpose : Radiotherapy with concurrent chemotherapy has been recommended as standard treatment for locally advanced cervical cancer. To validate the main tumor location before each high-precision helical tomotherapy (HT) fraction, the development of a more reliable marker or indicator is of clinical importance to avoid inadequate coverage of the main tumor. Material and methods: A 61-year-old woman with cervical cancer, TMN stage cT2b2N1M1, FIGO stage IVB was presented. Extended field external beam radiotherapy (EBRT) with concurrent chemotherapy and the interdigitated delivery of intracavitary brachytherapy was performed. Helical tomotherapy equipped with megavoltage cone beam computed tomography (MV-CBCT) was used for image-guided radiotherapy. For the insertion of tandem of brachytherapy applicator, a silicone sleeve with a central hollow canal was placed into the endocervical canal with the caudal end stopping at the outer surface of the cervical os, and making contact with the distal boundary of the cervical tumor during the entire brachytherapy course. Results : In the remaining EBRT fractions, we found that the air cavity inside the central hollow canal of the sleeve could be clearly identified in daily CBCT images. The radiation oncologists matched the bony markers to adjust the daily setup errors because the megavoltage of the CBCT images could not provide a precise boundary between the soft tissue and the tumor, but the sleeve air cavity, with a clear boundary, could be used as a surrogate and reliable marker to guide the daily setup errors, and to demonstrate the primary tumor location before delivery of each HT fraction. Conclusions : The application of the sleeve during the interdigitated course of HT and brachytherapy in this patient provided information for the feasibility of using the sleeve air cavity as a surrogate marker for the localization of the main primary tumor before the daily delivery of image-guided HT.